THE COMBINED TEMIMI TRANSFORM-DIFFERENTIAL TRANSFORM METHOD FOR SOLVING LINEAR NON-HOMOGENEOUS PDEs - HUSSEIN, NOOR ALI (Al-Qadisiyah Journal of Pure Science, 2017)
In this work, a combined form of Temimi transform method (TTM) with the Differential transform method (DTM) will be used to solve non-homogeneous linear partial differential equations (PDEs). The combined method is capable of handling non-homogeneous linear partial differential equations with variable coefficient.